Improving Student Achievement of Class I SD Negeri 7 Kontunaga in Mathematics Subjects Through Team Teaching Method - alifatah alifatah (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
This study aims to describe the improvement of student achievement in class I SD Negeri 7 Kontunaga in learning mathematics by applying the team teaching method. The benefits of this research are for students, teachers and schools. This research was conducted at SD Negeri 7 Kontunaga. The research subjects were first-grade students who found 17 students with details of 6 girls and 11 boys. Based on the data obtained from the results of research in two learning cycles, it can be explained as follows: (1) the results of 10 observations of student activities in the learning process with a total score of 27 with a value of 90.9 in the second cycle, the increase in value when compared to the first cycle scores a total of 13 with a value of 43.3 (2) the results of 9 observations of team teaching activities in learning with a total score of 24 with a value of 88.9 in the second cycle, an increase in value when compared to the first cycle a total score of 17 with a value of 62.9 and (3 ) learning achievement achieved by students showed a very significant increase, where in the second cycle there was an increase in the value of student learning outcomes with a class average of 85.00 and students who got a math score of 65 as many as 16 students (94.12%), there was an increase value when compared to the first cycle where the value of student learning outcomes with a class average of 70.59 and students who get Mathematics scores of 65 seb. There are 11 students (64.71%). The research concludes that applying the team teaching method in learning mathematics can improve the learning achievement of class I students at SD Negeri 7 Kontunaga.